Implementation of the Constitutional Court Decision Regarding the Execution of Fiduciary Guarantees and Inclusion of Default Clauses in Indonesia - Badriyah, Siti Malikhatun; Suharto, R.; Marjo; Saraswati, Retno; Wafi, Muhammad Shafiyuddin (International Journal of Criminology and Sociology, 2021)
The existence of the Constitutional Court Decision Number 18/PUU-XVII/2019, made problems in society related to the implementation of the fiduciary guarantee execution. This study aims to determine and analyze the implementation of the Constitutional Court Decision Number 18/PUU-XVII/2019. The research method used is normative juridical by conducting document studies of legal principles, legal regulations and legal norms in Indonesia and interviews with civil law experts. The results showed that the decision of the Constitutional Court Number 18/PUU-XVII/2019, caused disagreements in its implementation. Prior to the Constitutional Court Decision, the execution of the Fiduciary Guarantee was based on the Fiduciary Guarantee Law, if the debtor in default, the Fiduciary Recipient can execute on the basis of the fiduciary recipient's own power to sell the object of fiduciary security, but with a Constitutional Court Decision it must go through a court. This creates confusion for creditors and is against the principle of material security. This is detrimental to creditors, because creditors cannot immediately sell their own fiduciary collateral objects if the debtor defaults. This phenomenon can lead to a lack of legal certainty and legal protection for fiduciary recipients and contradicts the nature of fiduciary guarantees which should have strong guarantee rights and are easy to implement.